Body Mass Index and Its Association with Genetically Transmitted Traits. (21st December 2020) - Alasmari, Sultan Z.; Eisa, Nashwa; Alshahrani, Saeed Mastour; Alam, Mohammad Mahtab; Rajagopalan, Prasanna; Makkawi, Mohammed
Abstract : Background . Body mass index (BMI) is a metric widely used to measure the healthy weight of an individual and to predict a person's risk of developing serious illnesses. Study the statistical association between genetically transmitted traits and BMI might be of interest. Objectives . The present study designed to extend the inadequate evidence concerning the influence of some genetically transmitted traits including ABO blood type, Rh factor, eye color, and hair color on BMI variation. Methods . A total of 142 undergraduate female students of the Department of Clinical Laboratory Sciences, Faculty of Applied Medical Sciences, King Khalid University, Abha, Saudi Arabia, were participated to investigate the possible linkage between genetic traits and BMI variations. Height and weight are collected from participants for BMI measurement. ABO blood type and Rh factor were determined by antisera. Results . Out of 142 female students, 48 were categorized in the first tertile (T1: less than 19.8 kg/m 2 ), 50 were categorized in the second tertile (T2: between 19.8 and 23.7 kg/m 2 ), and 44 were categorized in the third tertile (T3: greater than 23.7 kg/m 2 ). Chi-square analysis shows that there were no associations of genetic traits including hair color, eye color, ABO blood type, and Rh blood type with BMI. However, a significant association between hair color and BMI was observed using multinomial logistic regression analysis. Conclusions . Our data provides a more robust prediction of the relative influence of genetic effects such as hair color on BMI. Future studies may contribute to identifying more association between genes involved in hair pigmentation and BMI variation.